Talent Is Everywhere, Opportunity Is Not: Online Role Model Mentoring and Students' Aspirations - Pietro Biroli; Amalia Di Girolamo; Giuseppe Sorrenti; Maddalena Totarelli (Institute of Labor Economics (IZA), 2025)
Educational disparities often limit students' access to relatable role models, constraining their aspirations and educational outcomes. We design and implement the Online Role Model Mentoring Program (ORME), a scalable, low-cost intervention connecting middle school students with successful role models from similar backgrounds. Using a randomized controlled trial with over 450 students in Campania, Italy, we find that ORME improves students' beliefs about the returns to effort, increases alignment between aspirations and expectations, and boosts school effort. Treated students also become more academically ambitious: they are more likely to enroll in academically oriented tracks and perform better on standardized language tests. These findings show that brief online mentoring sessions can have a meaningful impact on students' attitudes and choices at a critical stage of schooling, highlighting a promising tool to support students in low-opportunity contexts.
Keywords: I21; I24; J24; D91; 330; role models; aspirations; mentoring; school interventions